Mechanical Properties of a Lithium Disilicate Strengthened Lithium Aluminosilicate Glass‐Ceramic. Issue 2 (30th December 2013) - Laczka, Maria; Laczka, Karolina; Cholewa‐Kowalska, Katarzyna; Kounga, Alain B.; Appert, Christoph; Reimanis, I.
<x xml:space="preserve">Abstract</x> A glass composition in the Li2O–Al2O3–SiO2 (LAS)‐ternary phase diagram is presented, which enables the crystallization of Li2Si2O5 as well as LiAlSi2O6 upon a well‐defined heat treatment. Li2Si2O5 is the minor crystalline phase in the glass‐ceramic and generates through the bulk strengthening of the LAS glass‐ceramic. A flexural strength as higher as 400 MPa is measured in the proposed glass‐ceramic formulation, thus outperforming conventional LAS‐glass‐ceramics. A combination of the presence of those two crystalline phases of very different mechanical properties and coefficient of thermal expansion as well as the microstructure are believed to contribute largely to the enhancement of the measured properties.